A case report of hemophagocytic syndrome induced by Brucella melitensis biovar 3 - Wei, Chao; Zhang, Huan; Chen, Jing; Gu, Xiu; Tong, Mengwei; Zhou, Yang; Yun, Minghui; Zhang, Kaiting; Chen, Tao; Xie, Songsong (Frontiers in Immunology, 2025)
Hemophagocytic syndrome (HPS) is also called hemophagocytic lymphohistiocytosis (HLH). Hemophagocytic syndrome caused by Brucella infection is a rare and life-threatening complication. We report a case of a 55-year-old female farmer from China, whose symptoms included fever, pancytopenia, and liver damage. Early on, we identified the phenomenon of hemophagocytosis through blood culture and bone marrow examination, thereby confirming the case. The pathogen was precisely identified as Brucella melitensis Biovar 3 using AMOS-PCR technology and a systematic evolutionary analysis of the IS711 sequence, which was highly homologous to a strain of badger isolated from the same area previously. This provided molecular evidence for the potential animal-to-human transmission chain from wild animals. The patient received combined treatment with anti-infective drugs (doxycycline and rifampicin), corticosteroids, and intravenous immunoglobulin, and then followed a stepwise dose reduction treatment plan. After discharge, we conducted personalized follow-up management for the patient. This case highlights the potentially fatal complications that brucellosis can cause — hemophagocytic syndrome — and it is particularly common among individuals in high-risk occupations. For patients with brucellosis accompanied by unexplained blood cell reduction and abnormal liver function, a bone marrow puncture examination should be conducted as soon as possible. In the subsequent treatment, a combined treatment plan of “antibiotic therapy plus immunomodulation” can be adopted. Furthermore, it highlights the emerging zoonotic threat posed by B. melitensis biovar 3 in endemic areas.